Development and Use of the Leadership Competencies for Healthcare Services Managers Assessment - Hahn, Cynthia A.; Gil Lapetra, Marisa (Frontiers in Public Health, 2019)
Healthcare management as a profession continues to evolve as the field of healthcare delivery becomes more complex. In some countries, formal degree programs in healthcare management and related professional associations have helped to establish the field as a distinct profession with a defined body of knowledge. In other countries, the professionalization of healthcare management has not developed, or is in the early stages of development. Many of these Low and Middle Income Countries (LMIC) have no formal training programs or professional associations to help set and define minimum standards and competencies for the profession. In many countries, national associations have been created by healthcare managers for sharing knowledge, information and expertise. While major differences exist in the contexts where healthcare managers operate around the world, all have a common responsibility to enhance the leadership and managerial capacity and capability of their membership as well as promote the profession they represent . In spite of these efforts by national professional organizations and various ministries of health, healthcare management has not been universally recognized around the world as a profession. The Leadership Competencies for Healthcare Services Managers (Global Competencies Directory) framework developed by the International Hospital Federation’s global consortium for healthcare management serves as a catalyst and resource for defining the skills, knowledge and abilities needed for the healthcare management profession. This article documents the purpose, development, validation and use of the framework.